2016
DOI: 10.1038/cddiscovery.2016.85
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of VDAC trafficking modulates cell death

Abstract: The voltage-dependent anion channel (VDAC) and mitochondria-associated hexokinase (HxK) have crucial roles in both cell survival and death. Both the individual abundances and their ratio seem to influence the balance of survival and death and are thus critical in scenarios, such as neurodegeneration and cancer. Elevated levels of both VDAC and HxK have been reported in cancerous cells. Physical interaction is surmised and specific residues or regions involved have been identified, but details of the interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…The nucleus sometimes shows some decoration as well, but this could be caused simply by ribosomes originating from the continuation of the nuclear membrane into rough endoplasmic reticulum (RER). The mitochondrial outer membrane is not connected with RER and features different properties such as large amounts of voltage gated anion channels (VDAC; Dubey et al, 2016) or associated proteins [e.g. hexokinase (HxKII; Colombini, 1983)] that could be a potential anchor points for the ribosome association observed here.…”
Section: Resultsmentioning
confidence: 96%
“…The nucleus sometimes shows some decoration as well, but this could be caused simply by ribosomes originating from the continuation of the nuclear membrane into rough endoplasmic reticulum (RER). The mitochondrial outer membrane is not connected with RER and features different properties such as large amounts of voltage gated anion channels (VDAC; Dubey et al, 2016) or associated proteins [e.g. hexokinase (HxKII; Colombini, 1983)] that could be a potential anchor points for the ribosome association observed here.…”
Section: Resultsmentioning
confidence: 96%
“…Through its interaction with Bax and Bak, VDAC has been suggested to participate in the release of cytochrome c into the cytosol and the activation of the apoptotic cascade (Shimizu et al 2000 ; Tsujimoto and Shimizu 2000 ), while the anti-apoptotic Bcl-x L protein closes the pore by direct binding (Shimizu et al 1999 ). Hexokinase 1 binding to VDAC may suppress apoptosis by modulating VDAC activity and controlling the channel switching between off and on states (Caterino et al 2017 ; Dubey et al 2016 ). VDAC’s inhibition by tubulin could influence ATP trafficking, and even induce a switch, known as the Warburg effect, between oxidative phosphorylation and glycolysis in cancer cells (Maldonado et al 2013 ).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, in cancer cells under hypoxic conditions, a fraction of VDAC1 is truncated at the C-terminus (VDAC1-ΔC), and this was shown to confer resistance to cell death [70]. Likewise, it has been shown that VDAC1 over-expression-induced cell death occurs only when the protein is inserted into the mitochondria and proposed that VDAC1 trafficking modulates cell death and that this is regulated by the interaction with HK [71].…”
Section: Fig (1) Vdac1 Oligomerization Structures Interacting Sitmentioning
confidence: 99%